2011
DOI: 10.1590/s1516-80342011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do nível de satisfação de usuários de aparelhos de amplificação sonora individuais dispensados pelo Sistema Único de Saúde

Abstract: OBJETIVO: Adaptar culturalmente o questionário Satisfaction with Amplification in Daily Life (SADL), versão em Português Brasileiro, para administrar em usuários de aparelhos de amplificação sonora individuais (AASIs) dispensados pelo Sistema Único de Saúde (SUS). MÉTODOS: Participaram da pesquisa 19 sujeitos usuários de AASIs dispensados pelo Sistema Único de Saúde, por no mínimo três semanas, com idade igual ou superior a 60 anos, que apresentavam perda auditiva pós-lingual, sendo 63% do gênero masculino e 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 13 publications
(30 reference statements)
1
26
1
10
Order By: Relevance
“…We emphasize this topic to demonstrate that the literature does not record studies that assess simultaneously both the satisfaction with the service and with the device, and service evaluations is scarce (13) . Research that used other instruments to evaluate user satisfaction with their hearing aid (9,(15)(16)(17) , demonstrated higher levels relative to those in the present study. Within the view of quality control in treatment by health professionals, the user satisfaction index is pointed as one of the factors that must be analyzed.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We emphasize this topic to demonstrate that the literature does not record studies that assess simultaneously both the satisfaction with the service and with the device, and service evaluations is scarce (13) . Research that used other instruments to evaluate user satisfaction with their hearing aid (9,(15)(16)(17) , demonstrated higher levels relative to those in the present study. Within the view of quality control in treatment by health professionals, the user satisfaction index is pointed as one of the factors that must be analyzed.…”
Section: Discussioncontrasting
confidence: 58%
“…In one Brazilian (9) and one American (17) study, that utilized the IOI-HA, the majority of users made effective use of hearing aids and declared themselves satisfied with the device. In another study (15) , which used the questionnaire Satisfaction with Amplification in Daily Life (SADL), users registered high scores on all subscales of the instrument. However, this research contains a very limited sample when compared to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, monitoring satisfaction is important in the evaluation of clinical procedures and to ensure the quality of health services. Studies indicate that hearing aid users attended by the Brazilian public health system (SUS) and evaluated by the Satisfaction with Amplification in Daily Life (SADL) questionnaire (validated Portuguese version) were satisfied with the adaptation; the "personal image" scale was the most favored (18) . In another approach using the same instrument, the researchers concluded that the degree of satisfaction of adults who were supplied devices by the SUS was related to the type of hearing aid; the intraaural device was rated the best.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hearing aid users have difficulties with handling their hearing aids, which is one of the factors that can lead to malfunction of the prosthesis and its deterioration, thereby generating maintenance expenses 8,9 .…”
Section: Methodsmentioning
confidence: 99%